Circulating thyroid hormone levels in young pregnant rats and their fetuses: Effect of malnutrition - Mello, M. A. Rostom de; Oliveira-Filho, R. M.; Cury, L.; Souza Valle, L. B. (Karger, 1989)
In order to evaluate some factors likely to be involved in the maternal and fetal growth impairment due to alimentary protein deficiency, the circulating levels of triiodothyronine (T 3) and thyroxine (T 4) were studied in 4 young (45-day-old) female rat groups: control and malnourished, both nonpregnant and pregnant; similarly schedules groups were studied using adult (100-day-old) rats. Circulating levels of T 4 were higher in nonpregnant, malnourished young rats in their corresponding controls. T 3 levels were higher in young malnourished animals and lower in adult malnourished animals, nonpregnant or pregnant, as compared to controls. Pups from young malnourished mothers showed significantly lower birth weights than those from controls. The present results suggest that there are age differences in thyroid function, as affected by protein-calorie malnutrition in pregnant and non-pregnant rats. On the other hand, the circulating thyroid hormone levels were not importantly affected by the mother dietary protein restriction under our experimental conditions.
Keywords: Thyroid hormone; Animal experiment; Female; Growth; Nonhuman; Pregnancy; Priority journal; Protein restriction; Rat; Animal; Body Weight; Diet; Female; Fetus; Gestational Age; Nutrition Disorders; Pregnancy; Pregnancy, Animal; Rats; Rats, Inbred Strains; Thyroid Hormones; Thyroxine; Triiodothyronine